THE DIVERSITY OF BIRD TYPES IN BUKIT TANAH PUTIH SIDANGOLI, WEST HALMAHERA REGENCY - Nur Sjafani; Abdul Kadir Kamaluddin; Risal Sapsuha (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this study was to determine the diversity of bird species in Bukit Tanah Putih Sidangoli, West Halmahera Regency. Using the combined method of point count and line transects. Observations of bird samples were carried out in three types of habitats, namely the habitat of the trans Halmahera road, river lanes and white hills. Based on the results of the study, there were 59 species from 25 families with bird diversity index =2.70-3.39, the species evenness index ranged from 0.50 to 0.82. The evenness index value for the trans-halmahera mesh line in the garden vegetation type was higher (E= 0.82) compared to the vegetation index in the forest type (E = 0.69) and the HTI area (0.60). The highest evenness index value in Bukit Tanah Putih in the three vegetation types, namely gardens, forests and hearts, had the same evenness index value (0.50). The trans-halmahera road observation path is the most dominant species in garden vegetation, namely parrot parrot (Eclectus roratus), river location in Maluku serindit forest vegetation (Collocalia esculenta) and Bukit Tanah Putih in garden and forest vegetation (red cheek parrot = Geofroyi geofroyu). The conclusions of this study are the diversity of bird species in Bukit Tanah Putih, Sidangoli, moderate (H'=2.70) to high (H'3.39), the species evenness index was evenly distributed (E=0.50-0.82) and the high dominance.